Study on gene action and combining ability for yield and its attributes in upland rice lines of Himachal Pradesh - Garkoti, Priya; Pandey, Deo Prakash (Journal of Cereal Research, 2022)
The present study was conducted to estimate gene action and combining ability of 12 rice lines bred for upland conditions and 3 testers along with 36 cross combinations developed through line x tester mating design in Kharif 2019 and 2020. The crossing was done in Kharif 2019, and the material developed was grown and evaluated along with its parents in randomized block design in Kharif 2020. Statistical analysis of the observed data for 14 yield and yield related traits revealed that the dominance variance was higher than the additive variance for all the traits studied except total tillers per plant, grain breadth and L: B ratio. Moreover, the average degree of dominance was greater than 1 for most of the traits, indicating the preponderance of non- additive gene action in governance of these traits and the scope of exploitation of non- additive gene action for further improvement. Significant GCA and SCA effects were found for the lines and crosses, respectively. The lines showing significant GCA effects were HPR 2884, HPR 2871, HPR 2873, and HPR 2889, while the crosses HPR 2866 x HPR 2656, HPR 2866 x HPR 1156, and HPR 2840 x HPR 1156 showed high SCA for various traits.